Probiotics: an update on mechanisms of action and clinical applications - Goudarzi, Mehdi; Goudarzi, Hossein; Rashidan, Marjan (Novelty in Biomedicine, 2014)
Probiotics are live microbial feed supplement and can provide health benefit to the host if administered in sufficient amounts. The most predominant species that have been used as probiotic include Lactobacilli and bifidobacteria. Proper administration of probiotics could be efficient in the treatment of various disorders. However; their mechanism of action is poorly understood. The effects of probiotics may be classified in following modes: reinforcement of the intestinal mucosal barrier against pathogens, competition with pathogens for adherence to the mucosa and epithelium, competitive exclusion of pathogenic microorganisms, production of antimicrobial substances, modulation of the immune system and interference with quorum sensing signaling. Exploration of the clinical features of probiotic strains, their modes of action and investigation based on probiotic therapy may be beneficial in treatment of various diseases.